Clinical Boundaries of Trauma - Maayan Abargil; Dori Rubinstein; Alec Lerner; Erin Basol; Joliza Maynard; Tetiana Davydovska; Ilan Harpaz-Rotem (Journal of Nervous & Mental Disease, 2026)
Aim: Post-traumatic stress disorder (PTSD) rarely occurs in isolation; over 80% of individuals present with comorbid conditions such as depression, anxiety, or substance use disorders. The polythetic DSM-5 structure creates substantial diagnostic heterogeneity, producing thousands of possible symptom combinations. This theoretical paper seeks to demonstrate how trauma-related symptoms transcend diagnostic categories and proposes a mechanism-based framework for improving differential diagnosis and treatment planning. Methods: We review symptom overlap between PTSD and major depressive disorder, borderline personality disorder, prolonged grief disorder, and moral injury, highlighting discrepancies between DSM-5 and ICD-11 conceptualizations. Results: We demonstrate that trauma-related presentations reflect multidimensional suffering involving depression, dissociation, affective dysregulation, identity disturbance, grief, and moral distress. We propose a conceptual, mechanism-based framework organized around four response profiles, fear-based, grief-dominant, dissociative, and moral-injury patterns, that may capture underlying mechanisms more effectively than categorical diagnoses. Conclusions: A mechanism-based approach may refine diagnostic clarity, enhance treatment precision, and better integrate the psychological and somatic dimensions of trauma.